Changes in soil silicon forms and availability as affected by rice straw and its biochar. (2nd November 2022) - Yao, Donghui; Wu, Jianfu; Gao, Huiwen; Wu, Duoji; Wei, Zongqiang
Abstract: Phytogenic silica (PhSi) is suggested to control silicon (Si) cycling in soil–plant systems in tropical and subtropical regions. However, the role of crop residues and its biochar as a source of available Si has not been well investigated in agricultural soils. In our study, we determined and compared the effects of rice straw and its biochar on soil Si forms and Si availability. Soil Si forms were characterised by a sequential extraction method, and soil Si availability was assessed by rice growth and soil Si extraction methods. A soil incubation experiment showed that the addition of rice straw and biochar increased plant‐available Si in soil (including mobile Si and adsorbed Si), as well as soil amorphous Si (especially in rice straw treatments). Moreover, this increase was more significant when higher Si (e.g., Si added at the rates of 1.6 and 2.0 g kg −1 soil) was added via rice straw and its biochar, which is most likely a result of PhSi dissolution. Rice‐straw biochar, particularly at higher Si addition rates, tended to have a higher efficiency in increasing soil Si availability than rice straw, mainly due to its greater proportion of readily labile Si. A rice growth pot experiment showed that it is difficult to determine the extent of Si dissolution from PhSi in rice straw using a short‐term experiment with a normal single‐season straw return rate, where the increased pH played a more crucial role in regulating soil Si availability. Our results imply that, in terms of enhancing Si availability, long‐term biochar application with abundant Si input is more effective than straw retention for improving soil fertility in subtropical and tropical regions with highly weathered soils. Highlights: Effect of phytolith‐rich rice straw and its biochar on soil Si availability was studied. Biochar had greater efficiency in increasing plant‐available Si in soil than rice straw. Over the short term, Si dissolution from PhSi is insignificant with a typical single‐season straw return rate. Increased pH played a crucial role in regulating soil Si availability in a short‐term study.